Strategi Manajemen Keuangan Gereja Kalimantan Evangelis Dalam Bentuk Badan Usaha - Darnita, Cristi Devi; Triadi, Defri; Gobel, Della Gita Van (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
Financial management in religious organizations such as churches needs to be independent of church operational funds without relying on congregational offerings. The purpose of this study is to analyze the church's financial management strategy in managing its assets as an investment that generates funds for church management, especially in the Gereja Kalimantan Evangelis. The method used is a qualitative exploration with the techniques of observation, interviews, and documentation studies. This study analyzes the financial management strategy process namely strategy formulation, development of vision and mission, identification of opportunities and threats managing church assets at GKE Resort Tewah by building swallow nests and market blocks. The investment strategy results by managing church assets can fund all church operations and become a financially independent church without depending on congregational offerings. Manajemen keuangan pada organisasi keagamaan seperti gereja perlu menuju kemandirian dana operasional gereja tanpa bergantung pada persembahan jemaat. Tujuan dari penelitian ini adalah untuk menganalisis strategi manajemen keuangan gereja dalam mengelola aset yang dimiliki sebagai suatu investasi yang menghasil dana untuk pengelolaan gereja, khususnya di Gereja Kalimantan Evangelis. Metode yang digunakan adalah kualitatif eksplorasi dengan teknik observasi, wawancara, dan studi dokumentasi. Hasil penelitian ini berupa analisis proses strategi manejemen keuangan yaitu perumusan strategi, mengembangkan visi dan misi, mengidentifikasi peluang dan ancaman. Bentuk penerapan strategi keuangan dengan mengelola aset gereja di GKE Resort Tewah dengan membangun sarang burung walet dan blok pasar. Hasil dari strategi investasi dengan mengelola aset gereja dapat mendanai seluruh operasional gereja dan dapat menjadi gereja yang mandiri secara keuangan tanpa bergantung kepada persembahan jemaat.